Pediatric Refugee Health Care Delivery in the Community Setting: An Educational Workshop for Multidisciplinary Family-Centered Care During Resettlement - Umbereen S. Nehal; Satoko Kanahara; Mihoko Tanabe; Grace Hayner; Brett D. Nelson (Association of American Medical Colleges, 2020)
Introduction With 70.8 million people displaced worldwide, there is an increasing need for medical professionals to provide medical care to refugees. Insufficient training on refugee health poses a barrier to effective care delivery. Methods This workshop addressed common challenges in providing family-centered pediatric refugee care in community settings as well as barriers related to policy changes. Presentations covered prearrival experiences, medical screening, and trauma-based care. In small groups, participants discussed cases that featured medical, behavioral health, social, and cultural factors impacting the provision of family-centered pediatric care that was culturally respectful and included shared decision-making. After the breakout session, each small group informed the larger group of topics discussed. Facilitators identified themes and reinforced key learning points. At the workshop's conclusion, participants were guided to create their own personalized action plan. Results This workshop was presented at two international conferences to more than 47 participants, including clinicians, nurse practitioners, pediatric residents, and medical students. Evaluations were completed by 34 individuals. Participants' overall comfort level with taking care of refugee patients increased from 3.3 to 4.0 (on a 5-point scale, p = .24) during the 3-hour version of the workshop and from 3.8 to 4.0 (p = .43) in the 1-hour version of the workshop. Mean overall ratings of the 3- and 1-hour workshop versions on conference-administered evaluations were 4.8 and 4.2, respectively, on a 5-point scale. Discussions This workshop was well received and equipped participants with knowledge, tools, and strategies regarding pediatric refugee health in a community setting.